Analisis implementasi program food estate sebagai solusi ketahanan pangan Indonesia - Rasman, Alsafana; Theresia, Eliza Sinta; Aginda, M Fadel (Holistic: Journal of Tropical Agriculture Sciences, 2023)
Indonesia as an agrarian country with the majority of the population working in the agricultural sector does not guarantee that Indonesia will be free from a food crisis. The increasing population in Indonesia and the addition of the COVID-19 pandemic that occurred in 2020 affected food needs which resulted in food insecurity and affected the food supply chain. Food Estate is one of the strategies carried out by the Indonesian Government to overcome food security and the problem of the food crisis that is happening in Indonesia. The Indonesian government has issued several food estate policies and programs since the 1950s which were developed on a large scale with the aim of producing food needed by the community. However, in its implementation, the food estate project that has been carried out by the government so far has failed. So, this study aims to identify developments and analyse development problems from food estate practices by comparing practices in every food estate that has ever been carried out in Indonesia. In achieving the research objectives, a descriptive analysis method was used, namely by collecting data and studying the literature to obtain the key problem factors for the failure of food estate practices in Indonesia. The results of this study obtained information related to the failure factors of food estate project practices in Indonesia from the Old Order period to the present. The main factors causing the failure of food estates in Indonesia are the lack of mature development concept planning (plans for development locations, water availability, climatic conditions, technology, and synergy between the government and farmers), land ownership issues that cause conflict between the community and the government, resource capabilities farmers in managing agricultural land effectively, and the policies compiled by the government are considered to be unable to be implemented to maximize production yields and agricultural quality. Even the food estate program has caused environmental problems such as carbon release due to forest deforestation, biodiversity threats, reduced water catchment areas and flood disasters.